Research with children perspectives and practices - Christensen, Pia Monrad; James, Allison (Routledge, 2017)
"The entirely revised third edition of Research with Children forms a unique resource book on the methodology of childhood research with a core emphasis on theory driven practices. As in the previous two editions, this edition presents particular standpoints in the field, whilst also reflecting the latest developments in the now well-established interdisciplinary field of childhood studies."--Provided by publisher.